Integração do rio São Francisco às bacias do nordeste setentrional: abordagem malacológica, epidemiológica e laboratorial da transmissão do Schistosoma mansoni (sambon, 1907) em municípios cearenses - Castro, Issis Maria Nogueira (2018)
Schistosomiasis is a parasitic disease caused by trematodes of the genus Schistosoma, affects about 240 million people in 76 countries. B. glabrata, B. tenagophila and B. straminea are the three species of snails that are naturally infected by Schistosoma mansoni in Brazil, being only the last one involved in the transmission of the disease in Ceará. In the states bordering Ceará, B. glabrata has been observed. The development of water projects, such as the Integration Project of São Francisco River in the Northern Northeast Basins (PISF), has impacted the environment and, consequently, the transmission of schistosomiasis. With the conclusion of this water project there will be a mixture of water as well as the animals in it, among them the snails of the genus Biomphalaria. It should be noted that the population density of these mollusks is influenced by the physicochemical characteristics of the waters in which they live, and it is therefore important to know them for the construction of a baseline before the arrival of the waters of the São Francisco River. It is also important to determine the presence of eggs of S. mansoni in schoolchildren aged 7 to 14 years as an alternative to detect focal areas of the disease. In order to do it, we aimed to determine the malacological, epidemiological and laboratorial profile of Schistosomiasis Mansoni in areas of the Transposition of São Francisco River in the State of Ceará. Thus, the malacological research, the physical-chemical and microbiological analysis of the waters and the parasitological examination of feces by the Kato-Katz method was the methodology used to obtain the results. In relation to the population profile of the study, 604 students participated and in all six municipalities, the majority (57.65%) had a family income below a minimum wage. Of the 604 fecal samples analyzed, the presence of S. mansoni eggs was not evidenced. Of the 33 collection points in the 6 municipalities studied, in 9 (27,27%) the presence of Biomphalaria sp. was not evidenced and 100% of the snails collected did not eliminate S. mansoni cercariae. B. kuhniana was present in two points of collection of the municipality of Brejo Santo. Statistical analysis at all collection points showed that the conductivity (p = 0.0019) had a positive influence on the population density of the snails. Analyzing only the collection points where it was evidenced the presence of Biomphalaria sp. there was no statistical significance with any parameter. There were no positive cases for schistosomiasis in the studied population, as well as no elimination of S. mansoni cercariae in snails of the genus Biomphalaria, although this population presents characteristics that make it vulnerable to infection by S. mansoni. B. kuhniana was found for the first time in the state of Ceará. The physico-chemical and microbiological characteristics of the waters showed the adaptive capacity of these snails to inhabit a great variety of water collections.